Paradigma PARADIGMA INTEGRATIF-INTERKONEKTIF DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI MADRASAH - MUHAMMAD ISA ANSHORI; ALVIANI NUR BAITI ROHMA; WIDYA WULANDARI; DWI WULAN SARI (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2022)
The development of Islamic religious education curriculum in madrasas has become a real norm of the times that have complex problems. However, the reality is that the Islamic religious education curriculum is still unable to have a significant effect because it is still independent and reluctant to